A Study of the Effects of Saltwater on the Formation, Curing and Strength of Concrete - Khan , Anisuzzaman; Jannat, Syeda Rezwana; Md Abdul Basit; Islam, Md Monirul (IUBAT Review, 2023)
Concrete is extensively used in all construction works such as buildings, bridges, roads and dams worldwide. It is made by simply combining cement, aggregate, sand and water in the appropriate proportion. This paper explores the investigational study on the outcome of using saltwater in coastal regions for blending and curing concrete since palatable water is a deficient asset on the earth. As most of the ions in seawater comprise Na, Mg, Cl- and SO42-, this research aimed to observe how concrete behaves after the addition of NaCl and MgSO4 salt separately for mixing concrete and curing at different concentrations. Concrete cylinders were cured using fresh water as well as saltwater separately. A total specimen of 42 cylinders was cast with 100%, 75% and 50% ion concentrations of NaCl, MgSO4 and freshwater specimens prepared for the reference concrete, which were exhibited for 7 days and 28 days of curing. A comparatively higher compressive strength was found for a 50% salt concentration of MgSO4 and for 75% salt concentration of NaCl. The comparison of compressive strength using NaCl and MgSO4 samples between this research and previous researches was derived for 7 days and 28 days. A correlation between the compressive strength and ion concentrations of NaCl and MgSO4 for 28 days was derived by performing linear regression analysis. The relations obtained by this analysis can be utilized for further prediction of compressive strength at any other ion concentrations of these salts. IUBAT Review, 6(2): 25-40